2016
DOI: 10.1111/tid.12519
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of adenovirus infection of the urinary tract after renal transplantation

Abstract: Symptoms of all patients were alleviated, although some patients developed nephritis or viremia. Hence, the possibility of exacerbation should always be considered. Adequate follow-up observation should be conducted, and diligent and aggressive therapeutic intervention is required to prevent the condition from worsening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 18 publications
0
22
0
2
Order By: Relevance
“…[121][122][123][124][125][126] Although adenoviral infection in HSCT is more likely to cause severe disease than in SOT, there are reports of graft infection and rejection with adenovirus in essentially all SOT populations. 123,127,128 Infection in lung recipients is common (up to 22% in 1 series) and there are multiple reports of severe infection, including graft loss, progression to BOS, and death. 125,[129][130][131][132] Infection in HSCT recipients can be severe and associated with significant mortality.…”
Section: Adenovirusmentioning
confidence: 99%
“…[121][122][123][124][125][126] Although adenoviral infection in HSCT is more likely to cause severe disease than in SOT, there are reports of graft infection and rejection with adenovirus in essentially all SOT populations. 123,127,128 Infection in lung recipients is common (up to 22% in 1 series) and there are multiple reports of severe infection, including graft loss, progression to BOS, and death. 125,[129][130][131][132] Infection in HSCT recipients can be severe and associated with significant mortality.…”
Section: Adenovirusmentioning
confidence: 99%
“…9 Additional information is available from five renal transplant patients with ADV urinary tract infections treated with ganciclovir 5 mg/kg/ day for 5-7 days. 21 No adverse events were reported. The authors concluded that ganciclovir may be effective against ADV viremia.…”
Section: Discussionmentioning
confidence: 97%
“…Ganciclovir activity was first described in vitro from a fatal case of disseminated ADV in a pediatric liver transplant patient . Additional information is available from five renal transplant patients with ADV urinary tract infections treated with ganciclovir 5 mg/kg/day for 5–7 days . No adverse events were reported.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been described that the majority of patients presenting with haemorrhagic cystitis have an associated acute graft dysfunction, and in the large majority of patients, renal function returns to baseline after resolution of ADV infection . In the series reported by Watcharananan et al ., 11 of 17 patients (64.7%) showed an initial rise in serum creatinine, and kidney allograft pathology was described in three cases; tubulointerstitial nephritis (ADV nephritis), acute tubular necrosis, and acute rejection, suggesting that the incidence of concurrent ADV nephritis is not necessarily high among patients with haemorrhagic cystitis.…”
Section: Adv Infection In Kidney Transplant Patientsmentioning
confidence: 99%